Demographics and the natural real interest rate: Historical and projected paths for the euro area - Andrea Papetti (European Central Bank (ECB), 2019)
This paper employs an aggregate representation of an overlapping generation (OLG) model quantifying a decrease of the natural real interest rate in the range of -1.7 and -0.4 percentage points in the euro area between 1990 and 2030 due to demographics alone. Two channels contribute to this downward impact: the increasing scarcity of effective labor input and the increasing willingness to save by individuals due to longer life expectancy. The decrease of the aggregate saving rate as individuals retire has an upward impact which is never strong enough. Mitigating factors are: higher substitutability between labor and capital, higher intertemporal elasticity of substitution in consumption, reforms aiming at increasing the relative productivity of older cohorts, the participation rate and the retirement age. The simulated path of the natural real interest rate is consistent with recent econometric estimates: an upward trend in the 70s and 80s and a prolonged decline afterward.
Keywords: E17; E21; E43; E52; J11; 330; demographic transition; aging; natural interest rate; secular stagnation; euro area